Analisis Penyebab Ketidaksesuaian Stock Opname antara Sistem dengan Data Fisik Produk Carton Box Menggunakan Metode DMAIC pada PT PDP - Setiani, Ratri Apri; Sari, Rianita Puspa (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Inventory is one of the key elements in a company's operational success. In an effort to manage inventory well, companies often use systems to track, record and manage their stock. However, it is not uncommon for there to be a discrepancy between the amount of inventory recorded in the system and the actual amount in the storage warehouse. The purpose of this research is to determine the factors that cause discrepancies that occur in the physical data in the Carton Box storage warehouse with the data in the system. The approach method used in this research is the DMAIC method (Define, Measure, Analyze, Improve, Control) as a determinant of the main causal factors in the nonconformity. There are 4 factors that influence stock taking discrepancies during the March 2024 period, Of these 4 factors, the human factor is the factor that most influences stock taking discrepancies. The reason is because the physical pallet and transcript are different, there was an error in inputting data when making the travel document, there was an error in inputting the transcript document, the quantity of goods had not been upgraded and the placement of goods was not appropriate. The main cause seen from the largest percentage is because the physical pallet and transcript are different with the highest percentage being 36%. Keywords: Cartonbox, DMAIC,  Stockopname, Supply